The Urgency of IPR Registration as Protection of the Intellectual Work of Indonesian Lecturers - Pratiwi, Widya; Acfira, Lukytta Gusti Acfira; Juhana; Muhaimin Abdullah (Community Development Journal, 2024)
As times progress more rapidly, the existence and contribution of intellectual products, such as books and written works, in shaping the identity and progress of a society is becoming increasingly significant. However, with advances in technology and globalization, challenges to the security and protection of intellectual work rights are increasingly complex. It underlies the urgency of registering Intellectual Property Rights (IPR) as a real effort to protect creators' rights, motivate innovation, and build the foundation of a knowledge-based economy. Unfortunately, many academic lecturers do not realize the importance of having a creation registration letter. Some are aware but do not yet know the steps for managing copyright. Therefore, this community service is carried out as a presentation at a national seminar held by the Indonesian PkM Lecturer Association, which is carried out online to disseminate knowledge and information related to IPR. The participants are lecturers from all over Indonesia. Two general pieces of information are presented in the form of (1) education on the importance of IPR and the types of works that are protected and (2) steps for managing IPR and the documents required. It is hoped that this service activity can increase public awareness in general and academic lecturers in particular that IPR registration is not only a legal requirement but also a strategic step to form a society that respects creativity protects the rights of creators and encourages sustainable economic growth. Thus, this activity contributes to advancing knowledge in this country.